Single-layer MoS₂: a two-dimensional material with negative Poisson’s ratio - Zhu, Yucheng (2023)
Negative Poisson’s ratio (NPR) materials have broad applications such as heat dissipation, vibration damping, and energy absorption because of their designability, lightweight quality, and high strength ratio. Here, we use first-principles calculations to find a two-dimensional (2D) auxetic material (space group R (Formula presented.) m), which exhibits a maximum in-plane NPR of −0.0846 and a relatively low Young’s modulus in the planar directions. Calculations show that the NPR is mainly related to its unique zigzag structure and the strong interaction between the 4d orbital of Mo and the 3p orbital of S. In addition, molecular dynamics (MD) simulations show that the structure of this material is thermodynamically stable. Our study reveals that this layered MoS2 can be a promising 2D NPR material for nanodevice applications.